2010
DOI: 10.1007/s00044-010-9541-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial screening of N-(1-methyl-1H-pyrazole-4-carbonyl)-thiourea derivatives

Abstract: In the search of bioactive molecules in the class of functionally 4-substituted pyrazolic compounds, a series of N-(1-methyl-1H-pyrazole-4-carbonyl)-thiourea derivatives were prepared by addition of various substituted anilines to 1-methyl-1H-pyrazole-4-carbonyl isothiocyanate. The new thioureides and the intermediary compounds were characterized by spectroscopic data and elemental analyses and were evaluated for antibacterial and antifungal activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
(8 reference statements)
1
7
0
Order By: Relevance
“…[118] Limban and Missir prepared a series of thioureides of 2-(4-methyl/methoxy-phenoxymethyl)-benzoic acid with antimicrobial activity. [332][333][334][335] Similar antimicrobial activity against pathogenic bacteria and fungi were reported for chlorinated derivatives. [118] In similar fashion, thiourea derivatives bearing benzothiazole moiety possessed a broad spectrum of activity against microorganisms showing higher activity against fungi than bacteria.…”
Section: Biological Aspectssupporting
confidence: 54%
“…[118] Limban and Missir prepared a series of thioureides of 2-(4-methyl/methoxy-phenoxymethyl)-benzoic acid with antimicrobial activity. [332][333][334][335] Similar antimicrobial activity against pathogenic bacteria and fungi were reported for chlorinated derivatives. [118] In similar fashion, thiourea derivatives bearing benzothiazole moiety possessed a broad spectrum of activity against microorganisms showing higher activity against fungi than bacteria.…”
Section: Biological Aspectssupporting
confidence: 54%
“…A series of N -(1-methyl-1 H -pyrazole-4-carbonyl)-thiourea derivatives were prepared and evaluated for antibacterial and antifungal activities. Compound 209 was found to be the most potent antimicrobial agent [ 113 ]. The synthesis and antibacterial activity of pyrazole derivative were described by Tanitame et al Results showed that the compound 210 possesses potent antibacterial activity and selective inhibitory activity against bacterial topoisomerases ( MRSA , PRSA and VRE ) with MIC = 1–2 µg/mL [ 114 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Thioureas are important organic compounds possessing significant biological activities, act as corrosion inhibitors, catalyst and antioxidant, and are polymer components [1][2][3][4][5][6][7][8][9][10][11][12][13]. Moreover, the hydrogen-bonding ability of the thiourea moiety has been extensively used in the construction of anion receptors.…”
Section: Introductionmentioning
confidence: 99%